Frontmatter [Front Cover, Editorial Team, Indexing, and Table of Contents] - Purwanto, L.M.F (JoDA Journal of Digital Architecture, 2023)
Frontmatter [Front Cover, Editorial Team, Indexing, and Table of Contents]